Jugular Vein Aneurysm, When We Have to Do Surgery? - Rizki Amalia; Johanes Nugroho; Ivana Purnama Dewi (HM Publisher, 2021)
Introduction: The most common lesions of jugular vein dilatation are aneurysms and ectasia. A jugular vein aneurysm is less common compare to an arterial aneurysm in adults. Because of the rare incidence, treatment guidelines primarily associated with the timing of surgery are not clearly established. Proper treatment can reduce patient complaints without excessive intervention. Case report: A 54 years old woman complained of swelling in the right neck that started three years ago and cephalgia for two years. From CT angiography, we obtained a jugular vein dilatation of 2.3 cm. During periodic evaluation from ultrasonography doppler, there is no increase in the size of the jugular vein. Conclusion: Jugular vein aneurysm presenting in adults is an infrequent phenomenon. It is a benign condition, and conservative observation is advised. It should be operated only if symptomatic or progressive enlarging. A periodic examination must be done to evaluate the size of the jugular vein before a surgical decision